Caveolin-1 enhances metastasis formation in a human model of embryonal rhabdomyosarcoma through Erk signaling cooperation. (1st May 2019) - Codenotti, Silvia; Faggi, Fiorella; Ronca, Roberto; Chiodelli, Paola; Grillo, Elisabetta; Guescini, Michele; Megiorni, Francesca; Marampon, Francesco; Fanzani, Alessandro
Abstract: Rhabdomyosarcoma (RMS) is a pediatric soft tissue tumor classified in two major subtypes namely embryonal and alveolar, which have distinctive histopathological and genetic signatures and worse outcomes in the presence of metastases. Here, in order to evaluate the role of Caveolin-1 (Cav-1) in embryonal RMS dissemination, we employed an experimental in vivo metastasis assay using immunodeficient NOD/SCID mice. We found that the intravenous injection of human RD cells engineered for Cav-1 overexpression promoted the formation of lung metastases compared to parental cells. The arisen metastases were isolated and cultured in vitro to establish two derivative lines that showed greater metastatic capacity, as detected by performing in vivo metastasis and tumor spheroid invasion assays. Compared to parental cells, all metastatic lines were characterized by an increase in cell proliferation, migration and invasiveness that were downregulated by synthetic inhibition of Erk pathway. The metastatic cells showed a marked cell apoptosis induced by nutrient deprivation and consistent loss of differentiation characterized by depletion of MyoD and Myogenin factors. Furthermore, they showed marked changes in cell size, a re-organization of the three-dimensional cytoskeleton characterized by an increased actin stress fiber content, and increased adhesion and angiogenic properties. Collectively, these data provide new insights into Cav-1-driven metastatic process of embryonal RMS through cooperation of the Erk signaling pathway. Furthermore, our derivative metastatic lines represent useful tools for identifying genes or molecular pathways that regulate the metastatic progression of embryonal RMS. Highlights: The role of Cav-1 in embryonal rhabdomyosarcoma metastases was investigated. Cav-1 overexpression promoted Erk-dependent proliferation, migration and invasion in vitro and in vivo. Derivative metastatic lines showed a dedifferentiated cell phenotype. Metastatic lines have an altered cytoskeletal architecture and increased adhesion and angiogenic features. Cav-1 downstream targets represent a challenge to prevent embryonal RMS metastasis.